2019
DOI: 10.26508/lsa.201900465
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AXL receptor tyrosine kinase relates to monocyte dysfunction and severity of cirrhosis

Abstract: Immune dysfunction determines morbidity and mortality in liver cirrhosis. Distinct AXL-expressing circulating monocytes, which regulate antimicrobial responses, expand with progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(84 citation statements)
references
References 52 publications
(113 reference statements)
7
76
0
1
Order By: Relevance
“… 51 , 52 ) and are the main precipitant for hepatic acute decompensation (AD), with or without organ failure (acute-on-chronic liver failure [ACLF]) ( 53 , 54 ). Like ALF ( 3 ), cirrhosis and ACLF are associated with inflammation and, as disease progresses, immune dysfunction that contribute to increased susceptibility to infection ( 5 , 8 , 55 57 ). It would be important to further investigate the significance of the PD-1/PD-L1 pathway in cirrhosis, AD, and ACLF and its contribution to systemic and hepatic immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“… 51 , 52 ) and are the main precipitant for hepatic acute decompensation (AD), with or without organ failure (acute-on-chronic liver failure [ACLF]) ( 53 , 54 ). Like ALF ( 3 ), cirrhosis and ACLF are associated with inflammation and, as disease progresses, immune dysfunction that contribute to increased susceptibility to infection ( 5 , 8 , 55 57 ). It would be important to further investigate the significance of the PD-1/PD-L1 pathway in cirrhosis, AD, and ACLF and its contribution to systemic and hepatic immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence that AXL-CAR-T cell therapy has the potential to overcome the immunosuppressive TME by inhibiting the release of suppressive chemokines and cytokines from TAMs (67,68). In addition, since AXL expression is found on MDSCs, it is possible that CAR-T cells targeting AXL may deplete MDSCs from the TME and fundamentally alter the TME to a proinflammatory state (69). More recently, it was demonstrated that AXL-CAR-T cells with constitutive expression of the IL-7 receptor had enhanced in vitro anti-tumor activity and prolonged survival in a TNBC subcutaneous xenograft model (70).…”
Section: Receptor Tyrosine Kinase Axlmentioning
confidence: 99%
“…For example, expression of antigenic targets on both TNBC primary tumors and cells residing in the TME (e.g. MDSCs, TAMs, CAFs, Tregs), can facilitate CAR-T cell directed targeting of multiple cell types to overcome the immunosuppressive TME and enhance anti-tumor activity (69,76,94).…”
Section: Future Perspectives and Concluding Remarksmentioning
confidence: 99%
“…With respect to Axl, elevated serum levels of soluble Axl extracellular domain (sAxl) have been found to be a biomarker for hepatocellular carcinoma (Reichl & Mikulits, 2016), and mice lacking Gas6, the obligate Axl ligand (Lew et al, 2014), display enhanced tissue damage in a liver ischemia model (Llacuna et al, 2010). At the same time, Axl + monocytes are elevated in patients with cirrhosis (Brenig et al, 2020), and serum Gas6 and sAxl levels are elevated in patients with hepatitis C virus and alcoholic liver disease (Barcena et al, 2015). Divergent roles for Axl and Mer have been reported in chronic models of fibrosis, where Mertk −/− mice exhibited enhanced NASH development when fed a high-fat diet, whereas Axl −/− mice were protected (Tutusaus et al, 2019).…”
Section: Introductionmentioning
confidence: 99%